Serum antibodies against βH‐crystallins in the American Cocker Spaniel. (31st October 2013) - Kanemaki, Nobuyuki; Fukiage, Chiho; Ichikawa, Yoichiro; Shearer, Thomas R.; Azuma, Mitsuyoshi
Abstract Objective To detect antibodies for lens βH‐crystallins in the serum from the American Cocker Spaniel (ACS) presenting with and without cataracts and with and without uveitis. Animal Studied Seventy‐three American Cocker Spaniels and six normal Beagles. Procedures Sera were collected from 73 ACSs, including those with normal lenses and those with cataracts, or uveitis. Fractionated, normal Beagle lens βH‐crystallins were separated by one‐ or two‐dimensional electrophoresis. The separated lens βH‐crystallins were used on immunoblots as sentinel substrates against which the ACS sera were tested for the presence of antibodies against βH‐crystallins. Results Sera from approximately two‐thirds of study animals contained antibodies to some βH‐crystallin polypeptides, but reactivity varied among patients. Contrary to some hypotheses, serum antibodies to groups of βH‐crystallins did not relate to the stages of cataract. However, detailed analysis by two‐dimensional immunoblotting and mass spectrometry showed that three spots originating from βA1‐crystallin were detected only in sera from cataract patients. Conclusion Serum antibodies to βA1‐crystallin may be associated with the development of cataract.